Compressive Force‐Produced CCN2 Induces Osteocyte Apoptosis Through ERK1/2 Pathway. (May 2014) - Hoshi, Kenji; Kawaki, Harumi; Takahashi, Ichiro; Takeshita, Nobuo; Seiryu, Masahiro; Murshid, Sakhr A; Masuda, Taisuke; Anada, Takahisa; Kato, Ryushi; Kitaura, Hideki; Suzuki, Osamu; Takano‐Yamamoto, Teruko
ABSTRACT Osteocytes produce various factors that mediate the onset of bone formation and resorption and play roles in maintaining bone homeostasis and remodeling in response to mechanical stimuli. One such factor, CCN2, is thought to play a significant role in osteocyte responses to mechanical stimuli, but its function in osteocytes is not well understood. Here, we showed that CCN2 induces apoptosis in osteocytes under compressive force loading. Compressive force increased CCN2 gene expression and production, and induced apoptosis in osteocytes. Application of exogenous CCN2 protein induced apoptosis, and a neutralizing CCN2 antibody blocked loading‐induced apoptosis. We further examined how CCN2 induces loaded osteocyte apoptosis. In loaded osteocytes, extracellular signal‐regulated kinase 1/2 (ERK1/2) was activated, and an ERK1/2 inhibitor blocked loading‐induced apoptosis. Furthermore, application of exogenous CCN2 protein caused ERK1/2 activation, and the neutralizing CCN2 antibody inhibited loading‐induced ERK1/2 activation. Therefore, this study demonstrated for the first time to our knowledge that enhanced production of CCN2 in osteocytes under compressive force loading induces apoptosis through activation of ERK1/2 pathway. © 2014 American Society for Bone and Mineral Research.